2017
DOI: 10.3945/jn.117.248948
|View full text |Cite
|
Sign up to set email alerts
|

Maternal Dietary Patterns during Pregnancy Are Associated with Newborn Body Composition

Abstract: Maternal dietary intake during pregnancy may influence offspring growth and adiposity. Specific dietary patterns associated with newborn adiposity have not been identified. We aimed to identify patterns of maternal dietary intake associated with gestational weight gain (GWG) and fasting glucose during pregnancy and to evaluate whether adherence to these patterns is associated with newborn adiposity. In the Healthy Start prospective cohort, dietary intake during pregnancy was assessed via 24-h recalls. Reduced-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
50
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(55 citation statements)
references
References 45 publications
(55 reference statements)
4
50
0
1
Order By: Relevance
“…Greater FFM at birth may indicate better quality of maternal nutritional intake during pregnancy and healthier intrauterine experience of the fetus. In relation to this, a prospective study from Colorado, USA revealed that higher maternal consumption of solid fat, whole grain, fruits, cheese, poultry, nuts, and sugar during pregnancy predicted higher FFM at birth 48 . Another prospective study from the Netherlands showed that maternal protein intake (both animal and plant sources) during pregnancy predicted FFM but not FM at 6 years of age 49 .…”
Section: Discussionmentioning
confidence: 99%
“…Greater FFM at birth may indicate better quality of maternal nutritional intake during pregnancy and healthier intrauterine experience of the fetus. In relation to this, a prospective study from Colorado, USA revealed that higher maternal consumption of solid fat, whole grain, fruits, cheese, poultry, nuts, and sugar during pregnancy predicted higher FFM at birth 48 . Another prospective study from the Netherlands showed that maternal protein intake (both animal and plant sources) during pregnancy predicted FFM but not FM at 6 years of age 49 .…”
Section: Discussionmentioning
confidence: 99%
“…Because of the different intermediate variables, the DP extracted by RRR in existing studies were usually distinct from each other, so were the associations between DP and BW. Unlike our study, Starling et al used the gestational weight gain and the fasting glucose as the response variables in the RRR method and reported that a pattern characterised by starchy vegetables, eggs, non-whole grains, and a low intake of dairy products, dark-green vegetables, whole grains and soya was associated with greater newborn BW and adiposity (39) . Our results were also different from the findings of several previous studies that used the PCA method to extract DP.…”
Section: Discussionmentioning
confidence: 80%
“…DP1 obtained in our study was characterised by high intakes of legumes, soyabean products, vegetables, meat, dairy products, eggs and fish, with relatively low intakes of wheat and oils. This was partially different from the recognised healthy pattern, for example, the pattern recommended by the USDA, with higher intakes of fruits, vegetables, grains (with at least half of the intake from whole grains), moderate intakes of protein (such as low-fat meat and poultry, beans and legumes, nuts and seeds, or fish) and low-fat dairy products, and a limited intake of oils (with a preference for MUFA and PUFA), refined grains, and added sugars (39) . However, the dominant food groups of DP1 have benefits on BW, as were previously reported.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Maternal carbohydrate source in this study were mostly simple carbohydrate in the form of white rice or flour-based food. According to Starling et al (2017), pregnant women with high intake of eggs, starchy vegetables, and nonwhole grains was correlated with higher maternal fasting glucose and greater newborn adiposity, than the pregnant women with high intake of whole grains, poultry, nuts, and cheese.…”
Section: Maternal Characteristicsmentioning
confidence: 99%